A Fluorescent Nanoprobe Based on Graphene Oxide Fluorescence Resonance Energy Transfer for the Rapid Determination of Oncoprotein Vascular Endothelial Growth Factor (VEGF). Issue 11 (November 2013) - Wang, Sheng-E; Si, Shihui
Oncoprotein vascular endothelial growth factor (VEGF) is one of the most critical growth factors that regulates tumor growth and division. The vascular endothelial growth factor (VEGF) is also an important biomarker for different diseases and clinical disorders. Herein, we propose a graphene oxide (GO) fluorescence resonance energy transfer (FRET)-based aptasensor for rapid, sensitive, and selective detection of VEGF in homogeneous solution. The fluorescent dye-labeled anti-VEGF aptamer is adsorbed on the surface of GO via π-π interaction between the flat planar GO sheets and the ring structures in the nucleobases, which results in the fluorescence quenching of the dye due to the highly effective FRET from the dye to GO. Upon recognition and binding with the target VEGF, it specifically forms a VEGF/aptamer complex and then release from the GO surface, leading to the restoration of fluorescence signal of the dye. This GO-based sensing platform exhibits high sensitivity and specificity toward VEGF versus other proteins, with the detection limits corresponding to 2.5 × 10 −10 M. The sensitivity of this new type of aptamer-based assay is at least one order of magnitude higher than that of conventional homogeneous optical assays. Moreover, the application of this nanosensor for human serum sample analysis is also demonstrated. The GO/aptamer-based assay approach holds great promise as a general platform for detection of a variety of target molecules.